PENEGAKAN HUKUM PASAL 106 AYAT (6) UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALULINTAS DAN ANGKUTAN JALAN OLEH KEPOLISIAN SEKTOR MANDAU - Tri Apri Yanto; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Everyone in Indonesia using a motor vehicle to facilitate all their activities to mobilize or move from one place to another in the daily life. In Indonesia in the case of public awareness drive to use the safety belt still have not become a habit, whereas the use of safety belts is compulsory for drivers and passengers before the vehicles run or driven. As outlined in Act No. 22 of 2009 on Road Traffic and Road Transport. The purpose of writing this thesis are: First, to determine enforcement of Article 106 paragraph (6) the Act No. 22 of 2009 on Road Traffic and Road Transport Sector Mandau Police Department, Second, to determine the barriers in enforcement of Article 106 paragraph (6) the Act No. 22 of 2009 on Road Traffic and Road Transport Sector Mandau Police Department, Third, To know the efforts made to overcome obstacles in the enforcement of Article 106 paragraph (6) the Act No. 22 of 2009 on Road Traffic and Road Transport Sector Mandau Police Department.. This type of research can be classified into types of juridical sociological research. This research was conducted in the District Mandau, while the population and the sample is a whole party relating to the issues examined in this study, the data sources used, the primary data, secondary data, and the data tertiary, data collection techniques in this study with interviews, questionnaires , and literature. Analysis of the data used is qualitative data and techniques by means of deductive conclusion.. From the research, there are three main issues that can be inferred. First, law enforcement Article 106 paragraph (6) the Act No. 22 of 2009 on Road Traffic and Road Transport Sector Mandau Police Department is still not implemented optimally, Second, Obstacles encountered in enforcement of Article 106 paragraph (6) the Act No. 22 of 2009 on Road Traffic and Road Transport Sector Mandau Police Department will be influenced internal and external factors, Third, efforts are being made to overcome the obstacles in the enforcement of Article 106 paragraph (6) the Act No. 22 of 2009 on Road Traffic and Road Transport Sector Mandau Police Department through preventive and repressive measures. Author Suggestions, First, should the Police Sector Mandau firmly in taking a stance in enforcing the law, where the law looked at all the people are equal in front of him, Secondly, the necessary socialization, education, and related integrated deepening understanding of laws and regulations regarding the use of safety belts, Third, expected active role in enforcing the law enforcement and public participation in support of law enforcement carrying out their duties. Keywords: Implementation - Law Enforcement - Safety Belt